The Republic in danger : Drusus Libo and the succession of Tiberius - Pettinger, Andrew (Oxford : Oxford University Press, 2012)
The volume proposes a new model for understanding the end of Augustus' reign and the succession of Tiberius in the years 6 BC to AD 16. Focusing on Drusus Libo's role in an alliance between the enemies of Tiberius, Pettinger offers a comprehensive analysis of the struggle between Tiberius and the supporters of Augustus' grandsons.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 12, 2012).
Keywords: Tiberius, -- Emperor of Rome, -- 42 B.C.-37 A.D.; Libo Drusus, Marcus Scribonius; Rome -- Politics and government -- Republic, 265-30 B.C.; Rome -- Kings and rulers -- Succession; Rome -- History -- Tiberius, 14-37.